1996
DOI: 10.1080/02642069600000007
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of UK Investment Trusts

Abstract: The, Performance of 92 UK investment trusts was analysed over the period 1975 to 1993 using the Sharpe Treynor and Jensen measures ofportfolio performance. A very high degree of correlation was found betweenthe measures. Even without correction for transactions costs funds did not on average outperform the market, although a few individual funds appeared to do so. Fund rankings by the Sharpemeasure showedsignificant intertemporal persistence, especially in the income-producing group of funds, which needs furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 21 publications
2
25
0
Order By: Relevance
“…We also noted that the Sharpe and Treynor ratios rankings show a strong positive correlation. Our findings are similar to the findings of Bal and Leger (1996) and Casarin et al (2005) which indicated a very high correlation between the Sharpe and Treynor ratios.…”
Section: Resultssupporting
confidence: 82%
“…We also noted that the Sharpe and Treynor ratios rankings show a strong positive correlation. Our findings are similar to the findings of Bal and Leger (1996) and Casarin et al (2005) which indicated a very high correlation between the Sharpe and Treynor ratios.…”
Section: Resultssupporting
confidence: 82%
“…A significant positive (negative) slope coefficient is evidence of performance persistence (reversal); and, 3. Finally, a non-parametric two-way contingency matrix experiment employed by Goetzmann and Ibbotson (1994), Kahn and Rudd (1995), Malkiel (1995), Bal and Leger (1996) and Brown et al (1999) is adopted as a confirmatory measure. First, we sort the funds into winners and losers in period t-1 and winners and losers in period t. We distinguished winners from losers by ranking fund performance to the median performance, defining the above-median performers as winners and below-median performing funds as losers.…”
Section: Methodsmentioning
confidence: 99%
“…The persistence case, forwarded by Hendricks, Patel and Zeckhauser (1993), Goetzmann and Ibbotson (1994), Brown and Goetzmann (1995), Kahn and Rudd (1995), Bal and Leger (1996), Blake (1996b), Gruber (1996) 4 , Stewart (1998), andCarpenter andLynch (1999) report that past returns and relative rankings are useful in predicting returns and rankings in the short run (1 to 3 years). Grinblatt and Titman (1992) provide longer-term evidence of persistence (10 years), indicating that there is positive persistence in mutual fund performance.…”
Section: Previous Researchmentioning
confidence: 99%
“…2 Among the few studies of the mutual fund industry outside the US are Ward and Saunders (1976), Black, Fraser and Power (1992), Bal and Leger (1996), and Leger (1997), all of which investigate UK mutual fund performance.…”
Section: Introductionmentioning
confidence: 99%